The use of ethnographic research in product development : a study on the grocery packaging problems of elderly people - Wieland, Aliena; Wieland, Aliena (Massey University, 2011)
It is thought that one of the best ways to gain information for the development of new products and potentially the adaptation of older ones is through the use of ethnographic research during the development and research phase (Cooper & Edgett, 2008). The world‟s population is ageing and it has therefore become necessary to include elderly people more in the development of new products, particularly where research suggests they are encountering difficulties with grocery packaging, among other products. Product developers need to find solutions to these problems. The ethnographic research used in this study has been valuable in finding out what the problems are that elderly people are experiencing; how they are overcoming or getting around these problems, as well as what could potentially be done to develop appropriate solutions. It was found that elderly people are having difficulties with more traditional styles of packaging, like glass bottles, jars and aluminium cans, as well as some newer packaging types including ring-pull tin cans and freshness seals on milk bottles. These results are similar to those of previous research in this field (Duizer, Robertson, & Han, 2009) . Based on this ethnographic research and the above mentioned survey, it has been found that the current guidelines in place for packaging (shown in Table 1) are inadequate from an end users point of view, given that they focus primarily on function and environmental impact and less on openability. An adapted version of the Principles of Universal Design (Appendix VIII) would be immensely beneficial in helping to make the packaging industry more aware of the packaging problems elderly people are faced with, as well as ways to circumnavigate them.
Keywords: New products; Packaging; Food packaging; Packaging design; Elderly consumers